Kepuasan Penumpang Pesawat Udara Terhadap Pelayanan di Bandar Udara Samratulangi - Manado - Nurrasjid, M. N. (Warta Penelitian Perhubungan, 2011)
The services provided by operators of airports should be based on the needs and desires of service users, so that from these services will impact on satisfaction or dissatisfaction. To d.etermine the satisfaction of service users in Samratulangi-Manado airport passenger satisfaction research conducted on the service by using the analysis of the satisfaction index (customer satisfaction index), on 100 respondents of service users (passenger aircraft), the results of a study of services provided biJ operators of airports obtained value of 98.5%. The results of this study indicate that the service user (passenger aircraft) is venJ satisfied with the service that is felt during his stay at the airport.Keywords : Pe1formance Service, Satisfaction, Hope